1973
DOI: 10.1149/1.2403611
|View full text |Cite
|
Sign up to set email alerts
|

Interface Reactions of B[sub 2]O[sub 3]-Si System and Boron Diffusion into Silicon

Abstract: The interface reactions of the B2O3‐normalSi system were studied by infrared spectroscopy, electron and x‐ray diffraction, etc.The compound, which was produced at the B2O3‐normalSi interface in the temperature range of 900°–1200°C closely resembled SiB4 or SiB6 in the diffraction measurements. The growth rate of silicon oxide, produced in the interface in an oxygen atmosphere, was several times as fast as that in a nitrogen atmosphere. These growth rates are much faster than the ordinary growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 11 publications
6
48
0
Order By: Relevance
“…This method is very similar to that proposed by Taylor (9), and gives profiles substantially identical to those obtained with the first, more conventional method. At the end of the sputter etch the electron beam was focused on the edge of the sputtering crater and then scanned on a line across it.…”
Section: E Desupporting
confidence: 56%
See 1 more Smart Citation
“…This method is very similar to that proposed by Taylor (9), and gives profiles substantially identical to those obtained with the first, more conventional method. At the end of the sputter etch the electron beam was focused on the edge of the sputtering crater and then scanned on a line across it.…”
Section: E Desupporting
confidence: 56%
“…Arai et al (9) studied the compound produced during a boron deposition from various sources, and concluded that it was SiB~ and/or SiB6. Arai et al (9) studied the compound produced during a boron deposition from various sources, and concluded that it was SiB~ and/or SiB6.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is suspected that the generated silicon interstitials can be consumed by the BRL formation because BRL is known as a layer of silicon borides. [25][26][27] Then, the diffusivity decreases when BRL is formed at the surface. From this reason, C s must be replaced by C seff which is the effective surface boron concentration to have ability to generate the boron-silicon interstitial pairs and Eq.…”
Section: Boron Diffusion Modelmentioning
confidence: 99%
“…However, the particular challenge for boron diffusion process is the formation of Si-B x * corresponding author; e-mail: elamrani@msn.com compound named boron rich layer (BRL) [6][7][8][9][10] on the surface. This layer is detrimental for the surface and bulk carrier lifetime [11,12] and its removal is problematic [13].…”
Section: Introductionmentioning
confidence: 99%